2019
DOI: 10.4236/acs.2019.93022
|View full text |Cite
|
Sign up to set email alerts
|

Climate Study of Owerri and Comparative Analysis of Different Methods of Base Factor Computation

Abstract: This study analyzed three decades of the temperature and rainfall data of Owerri, South Eastern Nigeria and in the process carried out a comparative analysis of using three different methods namely the mean, median and jackknife to derive the base data upon which the anomalies are computed with a view to ascertaining if any significant differences exist in the obtained results. And for rainfall which is seasonal, a further z-score method was employed to remove the effect of seasonality by dividing the anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Urbanization transforms rural areas to urban within a decade resulting in the increased absorption of solar radiation, a decrease of evapotranspiration, and a release of anthropogenic heat, thereby resulting in a change of air temperatures, horizontal winds, and air quality. Several studies have shown that land use changes induce climate change [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization transforms rural areas to urban within a decade resulting in the increased absorption of solar radiation, a decrease of evapotranspiration, and a release of anthropogenic heat, thereby resulting in a change of air temperatures, horizontal winds, and air quality. Several studies have shown that land use changes induce climate change [13] [14].…”
Section: Introductionmentioning
confidence: 99%